2005
DOI: 10.1186/1471-2482-5-18
|View full text |Cite
|
Sign up to set email alerts
|

HEGPOL: Randomized, placebo controlled, multicenter, double-blind clinical trial to investigate hepatoprotective effects of glycine in the postoperative phase of liver transplantation [ISRCTN69350312]

Abstract: BackgroundKupffer cell-dependent ischemia / reperfusion (I/R) injury after liver transplantation is still of high clinical relevance, as it is strongly associated with primary dysfunction and primary nonfunction of the graft. Glycine, a non-toxic, non-essential amino acid has been conclusively shown in various experiments to prevent both activation of Kupffer cells and reperfusion injury. Based on both experimental and preliminary clinical data this study protocol was designed to further evaluate the early eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Thus, pharmacokinetics and pharmacodynamics of this substance and possible side effects, like wound healing deficiencies, are well known and well documented (Evins et al 2000;Luntz et al 2005).…”
Section: Control Glymentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, pharmacokinetics and pharmacodynamics of this substance and possible side effects, like wound healing deficiencies, are well known and well documented (Evins et al 2000;Luntz et al 2005).…”
Section: Control Glymentioning
confidence: 97%
“…Glycine is a simple amino acid that can be applied orally or intravenously without relevant toxicity (Luntz et al 2005;Kaufman et al 2009;Evins et al 2000;Gannon et al 2002). Besides being a major inhibitory neurotransmitter via the activation of the glycine receptor (GlyR) in central nervous system, glycine has been shown to protect against acute liver injury that occurs after warm or cold ischemia, or after toxic liver injury possibly resulting from the chemotherapy regimens commonly used for CRC Hoffmann et al 2011;Mikalauskas et al 2011;Schindler et al 2009;Zhong et al 2003;Schemmer et al 2002;Wheeler et al 1999;Amin et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There is no toxicity detected after oral or intravenous glycine application [7][8][9]. Furthermore, several studies have demonstrated that glycine prevents acute liver injury occurring after warm or cold ischemia by the inhibition of KC activation [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, several studies have demonstrated that glycine prevents acute liver injury occurring after warm or cold ischemia by the inhibition of KC activation [10][11][12][13][14][15]. This inhibition most likely occurs through a glycine-gated voltage-sensitive Cl channel in the surface membrane of the KCs [7,10]. After glycine binds to this channel, Cl ions enter the cell and hyperpolarize the KC membranes, which makes it more difficult to open Ca ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective randomized clinical trial on recipient preconditioning with glycine is currently ongoing [32]. Glycine and taurine preconditioning in steatotic rat livers were shown to be equally effective in the prevention of IRI, most likely via Kupffer cell-dependent mechanisms by decreasing interactions between leukocytes and platelets with endothelial cells and phagocytosis [33].…”
Section: Approaches For Preconditioning Organs In Order To Improve Trmentioning
confidence: 99%